KARAKTER MORFOLOGI TIGA KLON UBI JALAR DI MALUKU - Anna Y Wattimena; Reny Tomasoa; Marlita H Makaruku; Vilma L Tanasale; Martha Amba (Pattimura Proceeding, 2022)
Sweet potato (Ipomoea batatas (L.) Lam.) is one of the main carbohydrate sources in Mollucas and is a carbohydrate source food crop after rice, corn and cassava in Indonesia. In order to be able to identify the various characteristics of sweet potato clone collected, it is necessary to determine the morphological character of the genetic resource diversity characteristics that are most influential on sweet potato diversity. The aim of the study was to characterize the morphology of some sweet potatoes as potential yields in Mollucas. The results of the study were that the morphological characteristics of the three sweet potato clones in Mollucas had different colors, shapes on the leaves, stems, flowers, seeds and tubers